Living Hadith Study of Islamic Education Organizing Management in Central Aceh, Indonesia - Lukman, Jannah (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2024)
The application of the organizing Hadith in Islamic educational management is axiomatic and interesting to be studied because currently there are many Islamic educational institutions. This study explains how Hadith practices are integrated in Islamic educational institutions, especially in Central Aceh. This study aims to find out the life of the organizing Hadith which is the basis for Islamic education management. This study uses a field study method to collect information about the practice of organizing Hadith in society, namely the living Hadith study approach. After research, it was discovered that of the 9 educational institutions in Central Aceh, all of them had implemented organizing hadiths which include: Haditsh of choosing trustworthy leader; Hadith of obeying the leader; Hadith of choosing pious subordinates; Hadith of responsibility; Hadith of selecting capable subordinates; and Hadith of coordination. However, there are also subordinates who occasionally lack discipline in implementing Hadith so that they must be given sanctions because the rules must still be enforced to achieve the goals of Islamic education management. The hope is that through the implementation of this organizing Hadith, Islamic educational institutions will increasingly become a forum for advancing the community both in terms of management of facilities and the quality of human resources.